Predictors of burnout: the role of agency among obstetric providers in Kumasi, Ghana - Emma R. Lawrence; Michael Yeboah; Johnny Arthur-Komeh; Anna Stabnick; Sarah D. Rominski (Taylor & Francis Group, 2021)
Burnout rates among sub-Saharan African healthcare providers are high. In particular, obstetric providers experience unique stressors surrounding poor neonatal and maternal outcomes. This study explores predictors of burnout among obstetric providers at the Komfo Anokye Teaching Hospital (KATH) in Kumasi, Ghana. A survey was electronically distributed to midwives, house officers, and Obstetrician Gynecologists (OBGYNs) at KATH in Ghana. Demographic and clinical practice information was collected. Burnout was assessed using a 4-point Likert scale. To evaluate perceived agency caring for critically ill obstetric patients, participants responded to three statements and responses were summed to create an Agency Scale. Logistic regression was used to evaluate predictors of burnout. Marginal effects were calculated for factors significantly associated with burnout. Participants were 48 physicians and 222 midwives. Mean age was 32.4 years, mean years in practice was 6.5 years, and 83% had completed their medical training. Nearly half (49.6%) have personal experience with maternal mortality and 28.3% manage more than 5 maternal mortalities annually. The majority of participants (n = 152, 62%) reported feeling burned out from their work. After adjusting for role, number of annual maternal mortalities managed, and personal experience with maternal mortality, participants with more years in practice were 15.8% more likely to report being burned out (marginal effect = 0.158). Even after adjusting for years in practice, participants who scored higher on the Agency Scale had a significantly lower likelihood of reporting burnout (OR 0.76, 95% CI 0.66-0.88, p < 0.001). For each step up the Agency Scale, participants were 6.4% less likely to report they felt burned out. Rates of burnout are high among obstetric providers, particularly among providers who have practiced longer. Supporting provider agency to manage critically ill patients may reduce burnout rates.